(untitled) (Indian Journal of Animal Production and Management, 2014)
Twenty pigs from each breed of Ghunghroo, Niang Megha and crossbreds (50% Hampshire Boar X 50% Ghungroo Sow) maintained under similar managemental conditions at National Research Centre on Pig, Guwahati were selected for behavioural response studies with respect to varied THI. Also, a pilot study was conducted to observe the feeding behaviour of 20 adult Hampshire and Ghungroo pigs under different seasons (Summer - July and August & Winter - December and January). During summer season, difference in the percent of animals panting, using the covered space and postural variations among different breeds in response to heat stress was observed. Crossbreds suffered more, and among indigenous breeds, Niang megha was found to be suffered more as compared to Ghungroo. Niang Megha was found to be comparatively tolerant to cold stress as compared to Ghungroo and crossbreds. Heat production mechanism in term of average feed intake per minute was found to be more pronounced in Hampshire as compared to Ghungroo pigs. From the behavioural manifestations, the Ghungroo is found to be more adapted to the agro-climatic conditions of Assam as compared to Niang Megha and crossbreds.